2012
DOI: 10.1371/journal.pone.0050908
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET Imaging of Murine Atherosclerosis: Association with Gene Expression of Key Molecular Markers

Abstract: AimTo study whether 18F-FDG can be used for in vivo imaging of atherogenesis by examining the correlation between 18F-FDG uptake and gene expression of key molecular markers of atherosclerosis in apoE−/− mice.MethodsNine groups of apoE−/− mice were given normal chow or high-fat diet. At different time-points, 18F-FDG PET/contrast-enhanced CT scans were performed on dedicated animal scanners. After scans, animals were euthanized, aortas removed, gamma counted, RNA extracted from the tissue, and gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 44 publications
0
31
1
Order By: Relevance
“…The first clinical study with PET imaging of atherosclerosis, published in 2002 (17), was consequently performed using 18 F-FDG, which is a marker for uptake of glucose and hereby metabolism in tissue. The uptake of 18 F-FDG was later shown to correlate significantly with plaque macrophage content, with other circulating inflammatory biomarkers (18)(19)(20)(21) and known cardiovascular risk factors (6,22). Therefore, hope has risen that 18 F-FDG might be used to evaluate therapeutic intervention (23).…”
Section: Discussionmentioning
confidence: 99%
“…The first clinical study with PET imaging of atherosclerosis, published in 2002 (17), was consequently performed using 18 F-FDG, which is a marker for uptake of glucose and hereby metabolism in tissue. The uptake of 18 F-FDG was later shown to correlate significantly with plaque macrophage content, with other circulating inflammatory biomarkers (18)(19)(20)(21) and known cardiovascular risk factors (6,22). Therefore, hope has risen that 18 F-FDG might be used to evaluate therapeutic intervention (23).…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Thus, the evaluation of 18 F-FDG signal may be a useful approach to noninvasively monitor plaque inflammation and the effectiveness of therapies intended to alleviate inflammation in atherosclerosis. This method has successfully been adopted to murine atherosclerosis models, 18,26 although certain limitations still exist in terms of its feasibility for in vivo positron emission tomographic imaging. 27 Therefore, we focused on investigating the effects of MT-II on 18 F-FDG uptake by ex vivo analyses.…”
Section: F-fdg Uptake By Mt-ii 1351mentioning
confidence: 99%
“…In murine experiments, a strong correlation between FDG uptake and gene expression of inflammatory molecular markers has been demonstrated (21). Building on these early findings, in rabbits, it has been shown that inflamed aortic lesions accumulate up to 20 times more FDG than non-inflamed arterial lesions, thereby enabling reliable noninvasive detection of inflamed loci within arterial wall with FDG-PET (20).…”
Section: Basis For Arterial Fluorine-2-deoxy-d-glucose (Fdg) Uptake Fmentioning
confidence: 88%